PAEDIATRIC BASIC LIFE SUPPORT - Ivana Breznik; Matjana Koren Golja; Teja Markan; Eva Plut; Danijela Prelogar; Sara Spasenić (The Society for Children with Metabolic Disorders, 2024)
Children are not miniature adults. Resuscitating a child can be stressful for the staff. The education of healthcare professionals is crucial for fast, sure, and correct interventions. After each resuscitation, a debriefing session is recommended.